Full color generation with Fano-type resonant HfO2 nanopillars designed by a deep-learning approach. Issue 44 (31st October 2019) - Hemmatyar, Omid; Abdollahramezani, Sajjad; Kiarashinejad, Yashar; Zandehshahvar, Mohammadreza; Adibi, Ali
Abstract : Here, for the first time to our knowledge, a Fano resonance metasurface made of HfO2 is experimentally demonstrated to generate a wide range of colors. We use a novel deep-learning technique to design and optimize the metasurface. Abstract : In contrast to lossy plasmonic metasurfaces (MSs), wideband dielectric MSs comprising subwavelength nanostructures supporting Mie resonances are of great interest in the visible wavelength range. Here, for the first time to our knowledge, we experimentally demonstrate a reflective MS consisting of a square-lattice array of hafnia (HfO2 ) nanopillars to generate a wide color gamut. To design and optimize these MSs, we use a deep-learning algorithm based on a dimensionality reduction technique. Good agreement is observed between simulation and experimental results in yielding vivid and high-quality colors. We envision that these structures not only empower the high-resolution digital displays and sensitive colorimetric biosensors but also can be applied to on-demand applications of beaming in a wide wavelength range down to deep ultraviolet.